Audience and Social Criticism in Sisir Tanah Songs - Anang Masduki; Panqiang Niu; Rr. Octa Dwina Fauzia (ASSOCIATION FOR SCIENTIFIC COMPUTING ELECTRICAL AND ENGINEERING (ASCEE), 2020)
This research focuses on social criticism in an environment that is reflected in the lyrics of Sisir Tanah songs. The songs of Sisir Tanah are entirely focused on highlighting social issues, especially the environment in today's society. The purpose of this study is to describe audience reception as a resource person on how to see the role of Sisir Tanah songs as media to convey messages of social criticism. This research uses a descriptive qualitative method with a reception analysis method. The primary data is taken from the two songs of Sisir Tanah, namely Hidup and Bebal. The following data is obtained from interviews from several sources, journals, books, and the internet. The researcher also uses an interdisciplinary approach as a method of communication science studies whose lyrics are delivered by Sisir Tanah in the music media, social criticism theory, which describes Sisir Tanah into the category of social criticism in the environment, and the theory of respect analysis, which is the basis of the interview result of several speakers in interpreting the songs of Sisir Tanah. The results of this study show that social criticism through music media, in this case, is a song, is quite useful. Because the five speakers: Labib, Riska, Dedy, Sonnia, and Fachri, feel the social critique message delivered by Sisir Tanah through music becomes active when the listeners of the music can receive the message conveyed, as well as the effects obtained by the five speakers.